Factors Affecting Knowledge Pregnant Mothers About Malaria in the Work Area Harapan Health Center - Nihayatul Hasanah; Muji Lestari; Ika Wijayanti (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2021)
Malaria, one of the infectious diseases that is still a public health problem, especially in Papua, has an impact on the decline in the quality of human resources which can cause various social, economic problems, and even affect security stability. Data from the Papua Province Health Office in 2018 the Harapan Health Center was ranked second after the Kanda Health Center which had the highest malaria disease rate, namely there were 28 pregnant women with malaria out of 1,557 pregnant women, namely 1.7% of pregnant women with malaria. The purpose of this study was to determine the factors that influence the knowledge of pregnant women about malaria in the work area of the Harapan Health Center. This type of research uses a quantitative research design with a cross sectional research design. This research was conducted in the work area of the Harapan Health Center, from March to April 2020. The data analysis that will be carried out is in the form of univariate data analysis and bivariate data analysis, validated Questionnaire Research Instruments. Data collection through secondary and primary data, data processing through SPSS. p value : 0.220, experience 0.453, education 0.453, occupation 0.453, source of information 0.733, socio-cultural 0.629 which all 0.05. There is no relationship between age, experience, education, occupation, sources of information, socio-culture and knowledge. Key word: Knowledge Factors, Malaria, Pregnant Women